2005
DOI: 10.1126/science.1115273
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic H5N1 Influenza Virus Infection in Migratory Birds

Abstract: H5N1 avian influenza virus (AIV) has emerged as a pathogenic entity for a variety of species, including humans, in recent years. Here we report an outbreak among migratory birds on Lake Qinghaihu, China, in May and June 2005, in which more than a thousand birds were affected. Pancreatic necrosis and abnormal neurological symptoms were the major clinical features. Sequencing of the complete genomes of four H5N1 AIV strains revealed them to be reassortants related to a peregrine falcon isolate from Hong Kong and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
521
3
15

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(559 citation statements)
references
References 5 publications
6
521
3
15
Order By: Relevance
“…Although sporadic outbreaks in wild‐bird and poultry populations, with associated mortality because of this H5N1 HPAI virus were reported between 2002 and 2005, a virus representing a distinct sub‐clade of this Asian‐lineage was identified on Qinghai Lake, China in 2005, which displayed higher lethality and transmissibility for a wide range of wild birds 3 . The presence of a large population of migratory birds on Qinghai Lake is thought to have contributed to the spread of this highly lethal variant, now designated as a ‘Eurasian‐lineage’ clade 2.2 H5N1, 4 throughout Asia and into Europe and Africa 3 , 5 causing significant deaths in wild bird and poultry populations. In addition, there have been over 400 human HPAI H5N1 infections with a mortality rate of approximately 60% 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Although sporadic outbreaks in wild‐bird and poultry populations, with associated mortality because of this H5N1 HPAI virus were reported between 2002 and 2005, a virus representing a distinct sub‐clade of this Asian‐lineage was identified on Qinghai Lake, China in 2005, which displayed higher lethality and transmissibility for a wide range of wild birds 3 . The presence of a large population of migratory birds on Qinghai Lake is thought to have contributed to the spread of this highly lethal variant, now designated as a ‘Eurasian‐lineage’ clade 2.2 H5N1, 4 throughout Asia and into Europe and Africa 3 , 5 causing significant deaths in wild bird and poultry populations. In addition, there have been over 400 human HPAI H5N1 infections with a mortality rate of approximately 60% 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…We now recognize that avian migration can be an efficient mode of transport for avian microorganisms [16,33] and a catalyst for infection by endoparasites and pathogens [12]. Furthermore, with the emergence of highly pathogenic diseases such as avian influenza [16] and West Nile virus [20], avian migration has become a topic of multidisciplinary concern (e.g., [13,26]). …”
Section: Introductionmentioning
confidence: 99%
“…Prior to the recent HPAI subtype H5N1 outbreaks in ducks, host adaptation and lack of virulence in aquatic birds was cited as the reason for persistence in these species [32]. Recent studies in China have shown that viral lineages, established in poultry, have infected ducks [15,26].…”
Section: Introductionmentioning
confidence: 99%